2003
DOI: 10.1021/jp030508z
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Experimental and Theoretical Predictive Screening of Materials − A Comparative Study of Search Strategies for New Fuel Cell Anode Catalysts

Abstract: A comparative study of experimental and theoretical combinatorial and high-throughput screening methods for the development of novel materials is presented. Both methods were applied to the development of new anode fuel cell alloy catalysts with improved CO tolerance. Combinatorial experimental electrocatalysis was performed on a 64-element electrode array. Sputter-deposited ternary thin-film electrocatalysts of composition PtRuM (M = Co,Ni,W) were screened in parallel for their methanol oxidation activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
200
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 250 publications
(206 citation statements)
references
References 22 publications
5
200
0
1
Order By: Relevance
“…[17][18][19][20] Guided by first principle predictions of the CO tolerance of ternary Pt-Ru-M alloys, Strasser et al discovered an active class of Co-rich Pt-Ru-Co methanol oxidation catalysts. 21,22 The superiority of this system was later confirmed in an independent study by Cooper and McGinn. 23 The density functional theory (DFT) prediction suggested that Co exerts a ligand effect on Pt surface atoms, reducing the CO chemisorption energy.…”
Section: Introductionmentioning
confidence: 83%
“…[17][18][19][20] Guided by first principle predictions of the CO tolerance of ternary Pt-Ru-M alloys, Strasser et al discovered an active class of Co-rich Pt-Ru-Co methanol oxidation catalysts. 21,22 The superiority of this system was later confirmed in an independent study by Cooper and McGinn. 23 The density functional theory (DFT) prediction suggested that Co exerts a ligand effect on Pt surface atoms, reducing the CO chemisorption energy.…”
Section: Introductionmentioning
confidence: 83%
“…Density functional methods have over the past decade reached a level of maturity where they can be applied not just in detailed theoretical studies of a given material, but be used to search for novel materials for technologically relevant applications in materials science 4-10 and chemical engineering. [11][12][13][14][15][16] Such studies often take a screening approach where massive amounts of DFT calculations are performed using efficient semi-local approximations for the KS exchange-correlation (XC) energy and potential. These include generalized gradient approximations (GGAs) and recent meta-GGA (MGGA) functionals.…”
Section: Introductionmentioning
confidence: 99%
“…Beside experimental investigations, molecular simulations in conditions matching experiments are also of particular interest [4,29]. While density functional theory (DFT) simulations are able to predict both structure and composition of nanocatalysts leading to higher ORR efficiency, molecular dynamics (MD) simulations are able to predict their growth mode and the final possible structure when simulations are carried out with initial conditions consistent with experimental ones [30,31].…”
Section: Introductionmentioning
confidence: 99%